Peran Kepemimpinan Adaptif pada Transformasi Digital Organisasi - Ariedera Ariedera (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Digital transformation poses adaptive not merely technical challenges for today’s organizations. This study explores how adaptive leadership fosters successful digital transformation in large Indonesian service firms. Guided by adaptive leadership and dynamic capability theory, a convergent mixed‑methods design combined a multi‑case study of three firms with a survey of 237 managers analyzed using PLS‑SEM. Results show that adaptive leadership significantly boosts transformation readiness (β = 0.46, p < .001) and indirectly enhances project success through organizational agility. Qualitative insights reveal the value of structured “holding environments” that reconcile legacy and digital logics. The findings extend adaptive leadership theory to an emerging‑economy context and provide a grounded model for practitioners orchestrating technology‑enabled change.